OLD RELATIONSHIP OF INCIDENTS OF EARLY BREAKING WITH LEUKOCYTE RATES IN MATERNITY MOTHERS IN KARUNIA KASIH HOSPITAL BEKASI IN 2022 - Azhari, Dian Meisya; Khairiah, Rahayu (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background: The results of Long Form SP 2020 show that Indonesia has a maternal mortality rate of 189 which means that 189 women die during pregnancy, childbirth, or postpartum per 100,000 live births. maternal mortality rate in Indonesia has decreased. One of the causes of maternal death in Indonesia is due to infectious factors that cause KPD as much as (12%) (Ministry of Health of the Republic of Indonesia, 2020). Research Objective: The general purpose of this study is to determine the relationship between the length of premature rupture of membranes with leukocyte levels in maternity mothers at the Bekasi Gift of Love Hospital in 2022. Research Methodology: The methodology used in this study used a type of analytical observational research with a cross-sectional research design, the number of populations was taken from all data sources in one study, which was as many as 106 mothers. This study used secondary data in the form of data taken from medical records obtained manually. Research Results: The results of the study found a significant relationship between Leukocyte Levels and the incidence of Early Rupture of Amniotic Membranes at Karunia Kasih Hospital Bekasi obtained p value of 0.002. Conclusions and suggestions: from all these research activities, it can be concluded that there is a relationship between the length of premature rupture of membranes and leukocyte levels in maternity mothers at Karunia Kasih Hospital Bekasi. Therefore, it is expected that health efforts need to be maximally improved.